Isodon delavayi (Ocimeae, Nepetoideae, Lamiaceae): a new species from Yunnan Province, Southwest China - Yaping, Chen; Guoxiong, Hu; Chunlei, Xiang (Phytotaxa, 2014)
Isodon delavayi (Lamiaceae), a new and distinct species found in Mt. Yangyu of Yunnan Province, is described and illustrated. It is similar to I. scoparius and I. pharicus, but differs from the former by its much branched and shorter stems, entire leaves, and ovate-triangular calyx lobes, and from the latter by its entire and glabrous leaves, obsolete petiole, and less flowered cymes. Microfeatures of leaf epidermis, pollen grains, and mericarps of the new species are also presented.